Attautsikut/Together: understanding culture, change and success in Qitiqliq Secondary School and Arviat - Canadian Education Association; Maguire, Mary H.; McAlpine, Lynn (Toronto, Ont., Canada, Canadian Education Association, 1995, 1994)
Bibl.: p. 147-153.